Linking thought and text: The relationship between critical thinking and reading performance - Rengganis Siwi Amumpuni; Rudi Hartono; Dwi Rukmini; Rahayu Puji Haryanti (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2024)
The purpose of this study was to determine whether or not there is a correlation between the critical thinking skills of students and the level of reading comprehension that they demonstrate. To examine this relationship, the researchers employed a reading comprehension test adapted from the TOEFL proficiency framework alongside a critical thinking assessment. The data were evaluated using Pearson's Product-Moment Correlation, which demonstrated that there is a relationship between the two variables that is statistically significant. The results demonstrated a strong positive correlation between students’ levels of critical thinking and their reading comprehension scores. Moreover, students with high critical thinking abilities had significantly enhanced performance on the reading comprehension assessment relative to their peers with low critical thinking capabilities. These findings suggest that critical thinking plays a crucial role in the process of understanding written texts and may have meaningful implications for students’ academic development, particularly in the context of language learning.